Pengembangan e-modul berbasis flipbook maker untuk meningkatkan hasil belajar peserta didik pada kelas XII SMK - Dianawati, Ifa Afifah; Suputra, I Nyoman (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to develop an e-module based on a flipbook maker in the subject of Public Relations and Protocol Governance Automation to improve learning outcomes for class XII students of the Office Governance Automation Expertise Program at SMK PGRI 6 Malang. The model used by the researcher is Research and Development (RnD) with the Borg and Gall development model. Research and development used in research can be in the form of conceptual models, theoretical models, and procedural models. This study uses two types of data, namely quantitative data and qualitative data. Quantitative data consists of two types, namely data that comes from the results of the validation assessment of the flipbook maker-based e-module product by the validator. Qualitative research data, namely comments and suggestions from the subject of research trials and product development of flipbook maker-based e-modules. the results of the validation of material experts are 88, 33% are very valid, module experts are 91, 25% are very valid and field trials are 87, 27% are very valid.